2005
DOI: 10.1177/0142723705059114
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between mean length of utterance in morphemes (MLUm) and mean length of utterance in words (MLUw)

Abstract: Prior to Brown's (1973) introduction of mean length of utterance in morphemes (MLUm), child language researchers and speech-language pathologists used mean length of utterance in words (MLUw) as a measurement of a child's gross language development. After Brown (1973) and others documented MLUm to be a measure which was correlated with the development of morphological and syntactic skills in young children, the practice of counting MLUm became more widely used and accepted. In the present study, MLUw and MLUm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0
15

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 24 publications
5
89
0
15
Order By: Relevance
“…The comparison between MLU-m and MLU-w provided data that, while corroborated by international studies 32,33 , also reinforce findings of national studies with this same population 7,9 . The variables showed compatibility between them, indicating their use as language development measure.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The comparison between MLU-m and MLU-w provided data that, while corroborated by international studies 32,33 , also reinforce findings of national studies with this same population 7,9 . The variables showed compatibility between them, indicating their use as language development measure.…”
Section: Discussionsupporting
confidence: 78%
“…Studies 3,7,12,31,32 have shown the importance to consider MLU as a measure of language development, both for morphemes and words, also for individuals with DS. The comparison between MLU-m and MLU-w provided data that, while corroborated by international studies 32,33 , also reinforce findings of national studies with this same population 7,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural engagement was objectively measured using mean sentence length in words as an index of the child's motivation to engage with the learning task. Other measures of behavioural engagement could also be applied, such as the morphemic complexity of sentences produced, but research indicates that these two measures are almost perfectly correlated (e.g., Brown, 1973;Parker, 2005) and therefore we have favoured the simple method in our assessment of task engagement in this study.…”
Section: Methodsmentioning
confidence: 99%
“…However, the mean MLUm for the most verbal group, the established talkers, was less than 1.6-that is, even the most advanced children were mainly speaking in one-to two-word messages, at which point a child seldom uses inflectional morphemes (Owens, 2012). Therefore, it may be speculated that, for Hustad et al's toddlers, MLUm and MLUw measures would essentially have been equivalent (Parker & Brorson, 2005).…”
Section: Research Questionmentioning
confidence: 97%